Fabric flowers - Haxell, Kate (Tunbridge Wells, UK Search Press, 2011)
Kate Haxell has created twenty beautiful fabric flowers to adorn shoes, bags, clothes, hairclips or interiors, and they are all simple to sew. Learn how to make an embroidered felt daisy, a shabby chic flower, a folk-style flower in cool linen, a vintage tulle flower and much more, in fabulous fabrics and in styles to suit all tastes
Contents: Introduction - 4 Materials and techniques - 6 Feltie Mouse - 8 Apple Feltie - 10 Fuzzy Fish - 12 Starfish Feltie - 14 Rocking Robin - 16 Woolly Ewe - 18 Fuzzy Bunny - 20 Feltie Feline - 22 Perky Penguin - 24 Tortoise Feltie - 26 Snowflake Doll - 28 Ladybird Feltie - 30 Fuzzy Ted - 32 Russian Dolls - 34 Toadstool Feltie - 36 Perky Pig - 38 Caterpillar Feltie - 40 Fuzzy Owl - 42 Feltie Elf - 44 Feltie the Snowman - 46
1 2
Keywords: Decoration and ornament -- Plant forms; Sewing